IMPROVING WRITING RECOUNT TEXT BY USING EDMODO APPLICATION - Fitri Novia; Eva Saptarina; Lidia Resta (Universitas Islam Ogan Komering Ilir Kayuagung, 2022)
This paper's research purpose was to determine whether or not students who were taught using the Edmodo application and those who were not showed significantly different writing achievement. This study employed a quasi-experimental method. The samples were selected by using the purposive sampling method. Flipping a coin was used to decide which groups would be experimental and which would be control. Consequently, class IPS 1 was the experimental group while class IPS 2 was be control groups and each of them consisted of 30 students. The written test was conducted in order to gather the data. T-test was performed to assess the data. Based on the calculation of the independent sample test, it was found that t-obtained (14.511) was higher than t-table (2.001) and pvalue (0.000) was less than αvalue (0.05). In conclusion, the students who were taught using the Edmodo application indicated a significant difference from those who were not